2022
DOI: 10.3390/pharmaceutics14061187
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of QbD Approach to the Analytical Method Development and Validation for the Estimation of Metformin Hydrochloride in Tablet Dosage Forms by HPLC

Abstract: The current studies entail quality by design (QbD)-enabled development of a simple, rapid, precise, accurate, and cost-effective high-performance liquid chromatographic method for estimation of metformin hydrochloride (M-HCl). Design of experiments (DoE) was applied for multivariate optimization of the experimental conditions of the HPLC method. Risk assessment was performed to identify the critical method parameters (CMPs) using Ishikawa diagram. The factor screening studies were performed using a two-factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…The following are covered from the literature on QbD application in HPLC method development. Following the next steps, authentic literature search and initial risk assessment, analytical target profile (ATP) identifications, critical method attributes (CMA), risk assessment, and thane method optimization were performed [ 26 , 27 ]. Design Expert software, version 13.0.3.0, was used from Stat-Ease Inc., Minneapolis, USA.…”
Section: Experimental Workmentioning
confidence: 99%
“…The following are covered from the literature on QbD application in HPLC method development. Following the next steps, authentic literature search and initial risk assessment, analytical target profile (ATP) identifications, critical method attributes (CMA), risk assessment, and thane method optimization were performed [ 26 , 27 ]. Design Expert software, version 13.0.3.0, was used from Stat-Ease Inc., Minneapolis, USA.…”
Section: Experimental Workmentioning
confidence: 99%
“…The dose ratio of MET to SIT with 10:1 is one of the challenges for an analyst in developing a robust analytical method using the high-performance liquid chromatography (HPLC) technique. Nevertheless, analytical methods have been reported for simultaneous assay of MET and SIT using HPLC [4][5][6][7][8][9][10], and bio-analytical LC-mass spectrometry (LC-MS) [11,12] studies. From the reported HPLC methods, it was inferred that retention of MET on the C 18 column is very poor and causes the co-elution of impurities, even at column void.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, in a literature search on robust analytics, Hendy et al [6] reported an ultra-HPLC (UHPLC) method using the design of experiment (DoE) approach, but the study was not designed on the separation of impurities. Shat et al [7] employed quality by design (QbD) to determine MET in tablet dosage form, but not intended for simultaneous analysis [8]. Overall, there are no reports available on the QbD-based robust HPLC method for simultaneous assay of MET/SIT in the presence of their co-eluting impurities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional monomer model can be accommodated by the cross-linkers and the monomer's chemical connections. After polymerization, the template can be removed, revealing binding sites with new forms, sizes, and chemical characteristics [8][9][10][11]. A biguanide antihyperglycemic drug is metformin.…”
Section: Introductionmentioning
confidence: 99%